Mandibular posterior bone anchorage technique using steel wire: a retrospective descriptive study on dental movements and clinical tolerance - Grzelczyk Lucie; Ligerot Romain; Filippi Raphaël; Cresseaux Paul; Carlier Adélaïde (Journal of Oral Medicine and Oral Surgery)
Introduction: In 2015, a new technique for posterior mandibular bone anchorage, termed “Abalakov”, was introduced. This technique enables the distalization of mandibular teeth and the entire arch as needed, utilizing a single steel wire anchored to the internal oblique line of the mandibular ramus. This study aims to describe the dental movements achieved with Abalakov anchorage for targeted orthodontic adjustments. Secondarily, it profiles the patients who underwent this technique and evaluates their clinical responses, particularly regarding any signs of intolerance. Method: We conducted a retrospective descriptive study of patients treated by specialists in orthodontics and maxillofacial surgery in Lyon, France, from 2015 to 2023. A total of 32 cases involving 59 Abalakovs were analysed, gathering data on orthodontic treatment details, patient demographics, and post-operative effects. Results: The average molar retreat measured 3.70 mm (σ: 2.78 mm), and incisal straightening averaged 10.80° (σ: 8.13°). The rates of inflammation, infection, and loss of anchorage were 5.1%, 1.7%, and 13.6%, respectively, with class II decompensation was the primary indication with 84%. Conclusion: The Abalakov method appears to complement the therapeutic arsenal available to orthodontists and surgeons for the treatment of patients requiring solid mandibular posterior anchorage.